Plant fibre identification methods in research of heritage linen textiles - Suomela, Jenni (Helsingin yliopisto, 2024)
The doctoral thesis falls within the discipline of craft science, with the aim being to discover a means to identify plant fibres in heritage textiles. I have above all developed microscopy methods to separately identify flax (Linum usitatissimum L.), hemp (Cannabis sativa) and stinging nettle (Urtica dioica) fibres. The research material has also revealed the significant role played by cotton (Gossypium spp.) in linen textiles. This is the first research project to identify commercially cultivated cotton at the species level based on its fibre morphological properties. The existing literature often refers to textiles made of plant fibres using the general term linen because the material has been unidentifiable after production. My thesis offers tools for conducting detailed research on this type of textile. In the theoretical framework of the study, I have tied the knowledge gained from fibre identification to research models utilised in the deep analysis of objects. I have introduced natural scientific application methods through a focus on heritage science – a field of research not so well known in Finland yet. My research material consists of plant fibre textiles from different time periods in Finland, from surrounding areas and from the Khanty and Mansi peoples, also part of the Finno-Ugrian language family. The oldest material is from the Late Iron Age (12th century CE), namely fibre finds from the archaeological excavations of Ravattula, Ristimäki. The largest body of material derives from the textiles collected by the photographer I. K. Inha in White Karelia in the year 1894, but I have additionally utilised photographs and written resources. The cotton materials, dating as far back as the 14th century in Finland, represent recent archaeological and heritage finds. With respect to the fibre studies, the unique contribution of my research has been the development of new methods. I compiled a three-stage procedure that makes it possible to differentiate flax, hemp and nettle from each other by comparing ...